Association of maternal thyroid function and gestational diabetes with pregnancy outcomes: a retrospective cohort study - Zou, Chang; Shen, Qinxin; Yang, Yuanyuan; Liao, Yini; Du, Qiaoling (Frontiers in Endocrinology, 2025)
BackgroundGestational diabetes mellitus (GDM) and thyroid dysfunction share demographic overlap in at-risk populations, both exerting adverse effects on pregnancy. Their combined influence on pregnancy outcomes and complications requires further investigation through large-scale clinical studies.ObjectiveThis study aimed to compare trimester-specific thyroid function in a GDM population with a euthyroid population, and to examine the impact of maternal thyroid function on pregnancy outcomes after adjusting for GDM diagnosis status.MethodsThe retrospective cohort study involved singleton pregnant women registered between 2013 and 2020 in Shanghai, China. Maternal and infant biometrics were extracted from the electronic system at Shanghai First Maternity and Infant Hospital. The primary statistical methods in the study include logistic regression model and parallel mediation analyses.ResultsOf the 81,488 pregnancies included, 8,868 had GDM. Compared to the population without GDM, the GDM population exhibited lower free thyroxine (FT4) and different elevated thyroid-stimulating hormone (TSH) levels in specific trimesters. Mid-pregnancy thyroid function correlated with risks of preterm birth [for FT4<2.5th percentile while TSH>97.5th, adjusted odds ratio (OR)=2.471, 95% confidence interval (CI): 1.234−4.478] and fetal overgrowth (for FT4<2.5th percentile, adjusted OR=1.551, 95% CI: 1.271–1.874). Late-pregnancy low FT4 was associated with hypertensive disorders (for FT4<2.5th percentile while TSH>97.5th, adjusted OR=3.279, 95% CI: 1.221−7.375; for isolated FT4<2.5th percentile, adjusted OR=2.010, 95% CI: 1.260−3.057). GDM amplified all these risks. Moreover, maternal ferritin was a primary mediator in thyroid-neonatal weight associations, particularly in late pregnancy (mediation proportion: 22.1%).ConclusionThis study highlighted the increased risk of adverse outcomes associated with thyroid dysfunction in GDM pregnancies, underscoring the necessity for combined thyroid function and glucose metabolism screening, which facilitates timely interventions to mitigate risks of preterm birth, hypertensive disease, and fetal overgrowth.